Optimization of the process of drying of corn seeds with the use of microwaves - de Faria, Rute Quelvia; dos Santos, Amanda Rithieli Pereira [UNESP]; Gariepy, Yvan; da Silva, Edvaldo Aparecido Amaral [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Raghavan, Vijaya (Taylor & Francis, 2020)
The heating and drying of various types of food using microwave improve the economy of time and energy. The physiological quality variation of the seeds submitted to microwave drying is known to some extent. In this context, some authors have reported excellent performance using this technique, on germination rates, after drying. The commercial use of microwave drying in seeds is irrelevant, which motivates more extensive research on the benefits and challenges of this technique that can increase its insertion in the post-harvest handling steps of agricultural products. Corn is a product of high worldwide relevance. Therefore, the use of microwaves in its drying process has excellent potential to arrive at significant savings in its production. Thus, this study is aimed to evaluate the effects on the physiological quality of the seeds submitted to different drying conditions, using the microwave radiation. To that end, corn seeds, with a water content of 20% on wet basis (w.b.), were dried at 40, 50, and 60 °C, at power ratings of 0, 0.6, and 1.2 W/g; in the vacuum condition. Drying occurred continuously, with intermittent power, until the seeds reached the 12% wet basis; in this condition, the seeds could be stored with secure. Germination tests performed shortly after drying showed that the temperature of 40 °C at a power of 0.6 W/g had a reduction in drying time of approximately 5 h when compared to conventional drying (40 °C and 0.0 W/g). The evaluation of the physiological quality of the seeds showed no significant difference in the germination, vigor, and longevity indices of the treated seeds.
Keywords: Electro energy; magnetron; seeds longevity; vacuum microwave drying; vigor test